IMPLEMENTATION OF TAX PLANNING IN VILLAGE FUNDS - Nancy Mayriski Siregar; Nur Aliah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Tax Planning is a mandatory fiscal business strategy in such a way that the fiscal burden that is borne can be paid to a minimum. The data used is primary data, namely data from original sources and collected specifically, consisting of village profiles and budget plans for paving roads. The analysis technique used is descriptive quantitative. The method of data collection is documentation and direct interview methods. This research proves that the application of Tax Planning for Income Tax Article 22 and PPN is proven to be able to minimize the fiscal burden.